ANALISIS OLAHRAGA REKREASI TERHADAP PENURUNAN TINGKAT STRESS PADA PEKERJA KANTORAN YANG TERGABUNG DALAM KOMUNITAS TINJAL KABUPATEN LOMBOK TIMUR - Yuma Alfian; Lalu Sapta Wijaya K.; Fitri angarini Hari vanto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research aims to analyze the impact of recreational sports on reducing stress levels among office workers who are members of the Tinjal Community in East Lombok Regency in 2024. Using a quantitative approach, data were collected through questionnaires and documentation. The analysis, conducted with SPSS, showed a strong positive correlation (r = 0.938) between recreational sports and stress. The simple linear regression test revealed that recreational sports significantly affect stress (Sig = 0.000), explaining 87.9% of the variance. The findings suggest that the higher the participation in recreational sports, the more likely the reduction in stress levels among office workers. The alternative hypothesis, which states that recreational sports contribute to reducing stress levels, was accepted. On the other hand, the null hypothesis, asserting that there is no correlation or influence of recreational sports on stress reduction, was rejected. This study highlights the importance of recreational sports as an effective strategy to improve mental well-being and reduce workplace stress, providing valuable insights for workplace wellness programs.